Review Article about the Latest Medical Devices Used to Break Up Kidney Stones - Muftn, Sajjad Hadi Adnan; Mohammd, Sadiq Ali Abd al Hussein; Aziz, Mustafa Fahim Alwan; sakr, Muntadar Hakim Mohsen; Hussein, Haider Hassan Hamad (American Journal of Botany and Bioengineering, 2024)
The management of kidney stones has undergone significant advancements in recent years, with a focus on improving surgical techniques and device efficacy. The literature reveals a progression of methodologies and technologies aimed at enhancing stone fragmentation and retrieval, which are critical for effective treatment outcomes.